Relationships between rate of increase in post-exercise blood lactate concentration and performance of short-term high-intensity exercise in track athletes - Naoya Takei; Kenya Takahashi; Katsuyuki Kakinoki; Hideo Hatta (Japanese Society of Physical Fitness and Sports Medicine, 2018)
Over the past few decades, several studies have been conducted on the relationships between peak blood lactate concentration (PBLC) and exercise performance. However, it is still controversial whether PBLC has a correlation with exercise performance, and if it can be a reliable indicator for energy metabolism during short-term high-intensity exercise. Thus, the purpose of the present study is to establish a new reliable indicator. PBLC isn't able to reflect individual differences in kinetics of post-exercise blood lactate concentration (e.g. different time point of PBLC). Thus, to reflect the individual differences, we focused on the rate of increase in post-exercise blood lactate concentration (RIBLC). Twenty-two male university track athletes were divided into a sprinter group (S: n = 14) and middle- to long-distance runner group (ML: n = 8). 400-m (meter) time trials and blood samplings were conducted to measure exercise performance (average running velocity) and blood lactate concentration. In the present study, PBLC had no significant correlations with average running velocity in both S and ML. The present study supports previous studies that reported no correlations between PBLC and exercise performance. In contrast, significant correlations between RIBLC and average running velocity were observed in both S and ML (r = 0.69, p < 0.001 and r = 0.93, p < 0.01, respectively). RIBLC was significantly higher in ML than S (p < 0.05). It is assumed that RIBLC indicates lactate transport capacity and plays an important role in 400-m sprinting. Based on these results, RIBLC could be a new indicator for energy metabolism during short-term high-intensity exercise.